The dynamics of coordination in humanitarian clusters in Indonesia: Evidence from the cash working group coordination system during the 2022 Cianjur earthquake - Leonita Agustina Setyawati; Herdis Herdiansyah; Triarko Nurlambang (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: The increasing scale and complexity of disasters have intensified the need for effective coordination among multiple actors in humanitarian response systems. In Indonesia, the growing use of cash-based assistance has introduced additional coordination challenges, particularly within the Humanitarian Cluster Coordination framework. While existing studies highlight issues such as fragmented coordination and unclear roles, limited attention has been given to how coordination dynamics are formed in practice. This study aims to examine how coordination dynamics are shaped within the Cash Working Group (CWG) during the 2022 Cianjur earthquake response. Methods: This study employs a qualitative case study approach, based on in-depth interviews with 26 informants from government and non-governmental organizations, supported by document analysis. Data were analyzed thematically and interpreted using a coordination framework focusing on accountability, predictability, and common understanding. Findings: The findings show that coordination within the CWG evolves from informal communication toward more structured mechanisms, including formal meetings, joint decision-making, and operational guidelines. The intensity of coordination is found to be contingent upon contextual factors, particularly the scale of the disaster and the relative capacities of actors involved. Conclusion: Coordination in humanitarian cluster systems is adaptive and shaped by the interaction between formal structures and operational realities. Novelty/Originality of this article: This study provides empirical insights into the dynamic and hybrid nature of coordination in cash-based assistance within disaster response contexts.